Influence of pan-african parliament in regional decision- making on conflict prevention and resolution - Abanno, Ndidi Ugomma (University of the Witwatersrand, Johannesburg, 2023)
The establishment of the Pan-African Parliament as an institution of the African Union was prompted by the high incidence of conflict on the continent, and it is expected to play a role in addressing conflict. However, questions about the PAP's effectiveness in influencing regional conflict-related decision-making have arisen. The study used a combination of interviews, desk research, and participation in PAP sessions as a methodology for this study to explore this issue. The findings reveal that the PAP has consistently engaged in activities to prevent and resolve conflicts, such as debates on conflict-related issues in committees and the Plenary, fact-finding missions, promoting AU treaties, and developing Model Laws. However, the study also identifies factors limiting the PAP's influence in AU decision-making processes, including its limited legislative and budgetary powers and lack of coordination with pertinent AU institutions. To enhance its influence, the PAP needs to strengthen its institutional capacity to carry out non-legislative functions, particularly its oversight and representative powers. It must also establish a conflict intervention strategy and collaborative frameworks to improve synergies with AU institutions
A research report submitted to the Faculty of Management, University of the Witwatersrand, in 50% fulfilment of the requirements for the degree of Master of Management (in the field of Governance and Management) March 2023
Keywords: Pan-African Parliament; Politic; Conflict; Influence; UCTD; SDG-11: Sustainable cities and communities